Incidence of Low Birth Weight (LBW) in Wajo: A Cross Sectional Study - Nisa, Khaerin; Surahmawati, Surahmawati; Arranury, Zilfadhilah (Universitas Islam Negeri Alauddin Makassar, 2023)
Low Birth Weight (LBW) babies are babies with birth weight ≤ 2500 grams regardless of gestational period, whether premature or full term. LBW is a very complicated problem because it contributes to high morbidity and mortality, and can trigger chronic diseases due to instability of the baby's body in the future. This study aims to determine maternal factors associated with the incidence of low birth weight (LBW) in the work area of the Salewangeng Community Health Center, Wajo Regency. The type of research used is quantitative research using a cross sectional approach. The results of the study showed that there was a significant relationship between gestational age (p-value=0.000), consumption of iron/Fe tablets (p-value=0.000), ANC visits (p-value=0.000), consumption of fast food during pregnancy (p- value=0.000) with the incidence of LBW and there is no relationship between parity (p-value=0.601) and the incidence of LBW. Pregnant women are expected to make regular check-up visits during pregnancy and implement steps given by health workers to prevent the occurrence of LBW by doing physical activity, taking iron (Fe) supplements given by health workers and not frequently consuming fast food when pregnant. can affect the nutritional status of the mother and fetus.